Evaluation of the use of barrier contraceptives in women requesting termination of pregnancy at CHBAH - Maswime, Tumishang Mmamalatsi Salome (My University, 2015)
Introduction South Africa has a high prevalence of unintended pregnancies and HIV. Sixty eight thousand women die due to unsafe abortion annually worldwide, making it a leading cause of maternal mortality. In SA the maternal mortality has decreased from TOP. Maternal mortality from HIV is the leading cause of maternal mortality in South Africa. Unintended pregnancies are mainly a consequence of inconsistent and incorrect contraceptive use. The condom is the only contraceptive method which has the dual ability of preventing HIV and unintended pregnancies. We postulate that the failure of barrier contraception is a risk for both HIV and unwanted pregnancy. This study describes the contraceptive methods used by women at a TOP clinic and evaluates the use of barrier contraceptives amongst women requesting TOP, and the prevalence of HIV. Methods CHBAH is tertiary hospital in Southern Gauteng. Women with medical or surgical comorbidities that request a TOP are referred to the hospital. A prospective study using a cross sectional study design was performed at the Chris Hani Baragwanath Academic Hospital TOP clinic between February and October 2011. Data was collected using interviews and medical files. Results One hundred and nineteen women were interviewed. Most women 56 (47.06%) did not use any contraception at the time of conception. The most common reason for TOP was financial constraints, followed by relationship conflict. Pregnancy despite condom use was 34.45% (n=41). The percentage of women with condom failure, who were HIV positive was 34.14% (n=14). True condom failure was experienced by 12 women (pregnancy due to breakage/slippage of the condom. Conclusion Unintended pregnancy is mainly associated with not using contraceptives. The male condom was the most widely used contraceptive. The HIV prevalence in the group with condom failure was higher than the general antenatal population. There is a need for education regarding correct and consistent use of contraception.
A RESEARCH REPORT SUBMITTED TO THE UNIVERSITY OF THE WITWATERSRAND IN FULFILLMENT OF THE MASTER OF MEDICINE DEGREE
Keywords: Abortion, Induced; Contraception